The use of haystacks by wolves may facilitate the transmission of sarcoptic mange - Katarzyna Bojarska; Blanka Orłowska; Wojciech Sobociński; Małgorzata Karczewska; Marta Kołodziej-Sobocińska (Scientific Reports, 2024)
Abstract Wildlife that use anthropogenic resources often come into conflict with humans, e.g. due to damaged property, habituation or transmission of pathogens, amongst them Sarcoptes scabiei, the aetiological agent of sarcoptic mange, an emerging panzootic skin disease. This study examines the use of haystacks intended for supplementary feeding of European bison (Bison bonasus) by wolves (Canis lupus) with sarcoptic mange and the potential role of this behaviour in skin parasite transmission and human-wolf conflict. Hay samples from the beds used by wolves were found to harbour S. scabiei mites, even several days after the last use. Our data demonstrate an unforeseen link between wild ungulate supplementary feeding and wolf behaviour that may lead to conflict, namely approaching human settlements. However, no negative interactions were observed between wolves and humans or domestic animals. The presence of S. scabiei mites in haystacks provides a potential for its human-facilitated environmental transmission among wildlife and to domestic animals.